Rozwiąż równanie:
a) -3x-7=1-5x
b) 4(x+2)+3=5-2x


Odpowiedź :

Odpowiedź:

a) -3x-7=1-5x

-3x-7=1-5x

5x-3x=1+7

2x=8

x=4

b) 4(x+2)+3=5-2x

4(x+2)+3=5-2x

4x+8+3=5-2x

4x+2x=5-8-3

6x=-6

x=-1

Szczegółowe wyjaśnienie:

Rozwiąż równanie :

a)   - 3 x - 7 = 1 - 5 x

     - 3 x + 5 x = 1 + 7

     2 x = 8   /: 2

    x = 4

----------------------------------------------------

b)   4 (x + 2) + 3 = 5 - 2 x

     4 x + 8 + 3 = 5 - 2 x

     4 x + 2 x = 5 - 8 - 3

     6 x = 5 - 11

     6 x = - 6   /: 6

   x = - 1